High-entropy alloy material and preparation method and application thereof
By using MXene material as the substrate and using laser-induced solid phase to synthesize high-entropy alloy materials, the problem of efficient preparation of high-active and high-stability high-entropy alloy catalysts in the prior art is solved, and efficient photo-assisted catalytic performance is achieved, which promotes the development of photocatalytic zinc-air batteries and electrolytic water.
Patent Information
- Application Number
- CN202411983173.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to efficiently prepare high-entropy alloy catalysts with high activity and stability, especially in achieving photo-assisted catalysis.
Using MXene material as the substrate, the solid phase is directly induced by laser to synthesize high-entropy alloy materials, achieving uniform phase formation under ultrafast heating and high temperature conditions, and improving catalytic performance.
It has achieved efficient preparation of high-activity and high stability high-entropy alloy catalysts, with excellent photo-assisted catalytic performance, and improved the kinetics of oxygen precipitation reactions. It is suitable for the development and application of photocatalytic zinc-air batteries and electrolytic water.
Smart Images

Figure BDA0005221975060000111 
Figure BDA0005221975060000121 
Figure BDA0005221975060000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic materials, and in particular to a high entropy alloy material and a preparation method and application thereof. Background Art
[0002] The growing demand for energy and environmental crisis have prompted people to continuously develop renewable clean energy conversion and storage devices, such as water electrolysis devices and metal-air batteries. The important reaction processes involved in the above devices include oxygen evolution reaction (OER), but its slow reaction kinetics limit the efficient conversion and storage of energy. Therefore, it is urgent to develop highly active and highly stable catalysts to reduce the reaction energy barrier and achieve effective conversion and storage of clean energy. Photo-assisted electrochemical catalysts are an effective means of using sunlight to reduce the reaction energy barrier and improve reaction kinetics. Designing highly active catalysts with photo-assisted effects is of great research significance for promoting efficient energy conversion and storage.
[0003] High entropy alloys are homogeneous solid solutions composed of multiple metal elements. Their high mixing entropy gives them thermodynamic and kinetic stability, and the synergistic effect of multiple elements gives them excellent catalytic activity. Taking into account factors such as the differences in atomic size, atomic structure, and electronegativity of various elements, the successful synthesis of high entropy materials often requires extremely high temperatures and rapid heating and cooling to avoid phase separation. However, traditional heating methods such as tubular furnaces and hydrothermal methods have slow heating and cooling rates, which are not conducive to the preparation of high entropy nanomaterials. The development of efficient and economical high entropy material synthesis technology is still a challenge.
[0004] Nanosecond laser rapid heating technology is an emerging material synthesis technology in recent years. Laser heating technology is strongly dependent on the photothermal conversion effect of the substrate. The traditional carbon material substrate has a high thermal radiation rate, which reduces the utilization rate of laser energy on the one hand, and limits the temperature and heating rate of laser heating on the other hand. In addition, the interaction between the carbon material substrate and the catalyst is weak, which is not conducive to the improvement of stability. Therefore, a single carbon material substrate limits the research of multifunctional catalysts. Therefore, it is necessary to explore substrates with excellent photothermal conversion effect, strong support, and multifunctionality to synthesize high entropy catalysts, increase the reaction temperature, and explore the structure and properties of materials at ultra-high temperatures. In recent years, a series of high entropy nanomaterials have been successfully synthesized in a liquid environment. However, the liquid phase synthesis system requires cumbersome post-processing processes to separate the products, which is not conducive to large-scale production. The use of laser solid phase synthesis of high entropy catalysts with photo-assisted catalysis has not yet been reported.
[0005] Therefore, it is urgent to develop an efficient and simple process for preparing highly active, light-assisted high-entropy catalysts, improve the kinetics of oxygen evolution reaction, and promote the development and application of photocatalytic zinc-air batteries and water electrolysis. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a method for preparing a high entropy alloy material. Specifically, the method of the present invention uses a MXene material with excellent photothermal conversion effect as a substrate, and directly induces solid-phase synthesis of a high entropy alloy material by laser. Laser heating of the MXene material can achieve an ultra-fast heating rate and reach high temperature conditions, which is conducive to the formation of a homogeneous phase and improves the catalytic performance of the high entropy alloy material. Moreover, the method of the present invention is universal and is suitable for preparing a variety of high entropy alloy nanomaterials. At the same time, the method of the present invention can effectively reduce time costs and economic costs.
[0007] The present invention also provides a high entropy alloy material prepared by the above preparation method.
[0008] The present invention also provides the use of the high entropy alloy material as a catalyst or in the preparation of a catalyst.
[0009] According to an embodiment of the first aspect of the present invention, there is provided a method for preparing a high entropy alloy material, comprising the following steps:
[0010] A precursor solution containing a metal salt is mixed with a dispersion of MXene, and the mixture is dried to obtain a MXene loaded with a metal precursor; and the MXene loaded with a metal precursor is subjected to laser irradiation to prepare the high entropy alloy material.
[0011] The present invention provides a method for directly inducing solid-phase synthesis of high-entropy alloy materials using lasers, and realizes the in-situ synthesis of high-entropy nano-alloy materials based on MXene. The process of the present invention is simple, time-saving, and does not require the cumbersome post-processing process brought about by the liquid-phase synthesis system. Specifically, the present invention uses MXene as a substrate for laser irradiation: on the one hand, MXene has excellent photothermal conversion characteristics, and can achieve instantaneous high temperature by adjusting laser parameters. It is non-contact, easy to operate, easy to control the heating range, fast and efficient, and conducive to large-scale application in industrial production; on the other hand, the unique structural characteristics of the MXene surface enable it to stably and evenly load metal precursors without any additives.
[0012] According to some embodiments of the present invention, the process conditions of the laser irradiation include at least one of the following (a)-(f):
[0013] (a) The wavelength of the laser is 248 to 1064 nm;
[0014] (b) The power of the laser is 1 to 100 W;
[0015] (c) The laser spot diameter is 10 to 1000 μm;
[0016] (d) the pulse frequency of the laser is 10 to 100 KHz, for example, 10 to 80 KHz, 10 to 60 KHz, 20 to 60 KHz, 20 to 50 KHz, 20 to 40 KHz, 30 KHz;
[0017] (e) The pulse width of the laser is 5 to 100 ns, for example, 5 to 80 ns, 5 to 60 ns, 5 to 50 ns, 5 to 40 ns, 5 to 30 ns, 5 to 20 ns, or 10 ns;
[0018] (f) The scanning speed of the laser is 100 to 3000 mm / s, for example, 300 to 3000 mm / s, 500 to 2500 mm / s, 500 to 2000 mm / s, 800 to 2000 mm / s, 1000 to 2000 mm / s, 1250 to 1750 mm / s.
[0019] In the present invention, the average laser energy density can be adjusted (adjusted to 1-6 J·cm) by adjusting the laser spot diameter and pulse frequency. -2 , for example 1 to 5 J·cm -2 , 1.5~4J·cm -2 , 1.5~3J·cm -2 , 2~3J·cm -2 , 2.2~2.5J·cm -2 , 2.4J·cm -2 ), the material morphology and structure can be controlled by different heating times within a certain heating cycle.
[0020] According to some embodiments of the present invention, the MXene is selected from at least one of Ti3C2 and Mo2TiC2.
[0021] The MXene substrate of the present invention, such as Ti3C2, can be rapidly in-situ derived into TiO2, a material having a photoelectric effect, after being irradiated by laser, and can synergistically enhance the catalytic activity with high entropy nano alloy materials.
[0022] Compared with the MXene used in the present invention, although organic conjugated polymers such as polypyrrole and polydopamine also have photothermal conversion effects, they are completely decomposed under ultra-high temperature lasers (the preparation of high entropy materials usually requires more than 1000K), and the products cannot play a photo-assisted catalytic role. In addition, in metal nanomaterials / inorganic semiconductor materials, such as SiO2 / Au nanocomposites, SiO2 itself cannot absorb light and is not a suitable carrier for laser heating; although Au can absorb light, it is a precious metal and is expensive; on the other hand, simply mixing materials with light absorption and materials with catalytic activity will result in weak interaction between them, which is not conducive to the rapid transfer of photogenerated carriers and long-term cycle stability.
[0023] According to some embodiments of the present invention, the MAX original phase is etched using hydrofluoric acid to obtain the MXene.
[0024] According to some embodiments of the present invention, the MAX original phase is selected from Ti2CT x 、Mo2CT x , Mo2TiAlC2.
[0025] According to some preferred embodiments of the present invention, the MXene is Ti3C2, which is prepared by the following steps:
[0026] The MAX original phase is etched using hydrofluoric acid, other inorganic acids and intercalation agents to obtain the MXene.
[0027] According to some embodiments of the present invention, the other inorganic acid is selected from at least one of hydrochloric acid, sulfuric acid, and nitric acid, preferably hydrochloric acid.
[0028] According to some embodiments of the present invention, the intercalant is selected from at least one of lithium hydroxide, lithium chloride, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide, preferably lithium chloride.
[0029] According to some embodiments of the present invention, the MAX original phase is Ti2CT x .
[0030] According to some embodiments of the present invention, the mass ratio of the MAX original phase to hydrofluoric acid is 1:0.5-2.
[0031] According to some embodiments of the present invention, the mass ratio of the MAX original phase to the other inorganic acid is 1:1.5-3.
[0032] According to some embodiments of the present invention, the mass ratio of the MAX original phase to the intercalant is 1:0.5-2.
[0033] According to some more preferred embodiments of the present invention, the MXene is Ti3C2, which is prepared by the following steps:
[0034] Ti3AlC2 is mixed with hydrofluoric acid and other inorganic acids for the first time, and the solid and liquid are separated. The solid phase is mixed with the intercalation agent for the second time to obtain the product.
[0035] According to some embodiments of the present invention, the hydrofluoric acid is a hydrofluoric acid aqueous solution, and the concentration of the hydrofluoric acid aqueous solution is 5 to 10 wt %.
[0036] According to some embodiments of the present invention, the other inorganic acid is an aqueous solution of another inorganic acid, and the concentration of the aqueous solution of another inorganic acid is 8 to 15 wt %.
[0037] According to some embodiments of the present invention, the ratio of the mass of Ti3AlC2, the volume of hydrofluoric acid and the volume of other inorganic acids is 1 g: 2-3 mL: 4-8 mL. The present invention does not particularly limit the conditions of the first mixing, for example, it can be carried out at 30-40° C. for 12-36 hours.
[0038] According to some embodiments of the present invention, the solid-liquid separation further comprises washing the solid phase to neutrality.
[0039] According to some embodiments of the present invention, the intercalant is an intercalant solution, and the concentration of the intercalant solution is 10 to 30 mg / mL.
[0040] The present invention does not impose any particular limitation on the conditions for the second mixing. For example, the second mixing may be performed at 30 to 40° C. for 2 to 6 hours.
[0041] According to some preferred embodiments of the present invention, the MXene is Mo2TiC2, which is prepared by the following steps:
[0042] Mo2TiAlC2 is etched with hydrofluoric acid to obtain.
[0043] According to some embodiments of the present invention, the mass volume ratio of Mo2TiAlC2 to hydrofluoric acid is 1 g: 10-30 mL.
[0044] According to some embodiments of the present invention, the etching is performed at 50-60° C. for 48-60 h.
[0045] Atoms such as H, O, and F in the etching medium can bond with the MXene surface to form numerous surface end groups. The presence of these surface end groups causes significant chemical changes on the surface of the material. The present invention limits parameters such as the type of raw materials, the concentration of the etching medium, the reaction temperature, and the reaction time, and the prepared Ti3C2 has a suitable morphology and structure, and is more suitable for use as a substrate in the present invention.
[0046] According to some embodiments of the present invention, the metal salt is selected from at least one of cobalt salts, iron salts, nickel salts, chromium salts and molybdenum salts. According to some preferred embodiments of the present invention, the metal salt includes cobalt salts and iron salts. According to some preferred embodiments of the present invention, the metal salt includes cobalt salts, iron salts and molybdenum salts. According to some preferred embodiments of the present invention, the metal salt includes cobalt salts, iron salts, nickel salts and molybdenum salts. According to some preferred embodiments of the present invention, the metal salt includes cobalt salts, iron salts, nickel salts and molybdenum salts.
[0047] According to some embodiments of the present invention, the molar ratio of the cobalt salt, the iron salt, the nickel salt, the chromium salt and the molybdenum salt is 0.8-1.2: 0.8-1.2: 0.8-1.2: 0.8-1.2: 0.8-1.2.
[0048] According to some embodiments of the present invention, the ratio of the molar amount of the metal salt to the mass of MXene is 0.1-100mM:1g, for example, 0.1-80mM:1g, 0.1-40mM:1g, 0.1-30mM:1g, 0.1-20mM:1g, 1-100mM:1g, 10-80mM:1g, 10-40mM:1g, 15-40mM:1g, 20-40mM:1g, 30-40mM:1g.
[0049] According to some embodiments of the present invention, the mass ratio of the MXene to the metal precursor is 1:0.1-4, for example, 1:0.1, 1:0.2, 1:0.4, 1:0.5, 1:1, 1:2, 1:3, 1:4.
[0050] According to some embodiments of the present invention, the concentration of the metal salt in the precursor solution is 0.1 to 2 mol / L, for example, 0.2 to 1.2 mol / L, 0.2 to 1 mol / L.
[0051] According to some embodiments of the present invention, the concentration of MXene in the dispersion is 2 to 50 mg / mL, for example, 2 to 40 mg / mL, 2 to 30 mg / mL, 2 to 20 mg / mL, 5 to 20 mg / mL, 5 to 15 mg / mL.
[0052] According to some embodiments of the present invention, the precursor solution containing the metal salt and the dispersion of MXene are mixed at 20 to 35° C. for, for example, 20 to 40 minutes until they are in a uniform state.
[0053] According to some embodiments of the invention, the drying is freeze-drying.
[0054] According to some embodiments of the present invention, the laser irradiation is performed under a protective gas atmosphere, and the protective gas is selected from one of argon, a mixture of argon and oxygen, a mixture of argon and hydrogen, and ammonia.
[0055] According to some embodiments of the present invention, the laser irradiation comprises the following steps:
[0056] The MXene loaded with the metal precursor is prepared into a sheet with a thickness of 0.05 to 1 mm, placed in a closed transparent device with a gas connection, and allowed to stand for 5 to 20 minutes while passing argon gas;
[0057] Adjust the laser parameters and start laser scanning. The substrate temperature will rise rapidly to 1000-3000K within 1ms. After one scan, stop laser irradiation. The temperature will drop rapidly as the laser is removed. Continue to pass argon gas until the temperature drops to room temperature to obtain a high entropy alloy material.
[0058] According to an embodiment of the second aspect of the present invention, a high entropy alloy material is provided, and the high entropy alloy material is prepared by the above-mentioned preparation method.
[0059] The high entropy alloy material of the present invention has a homogeneous phase structure and has excellent catalytic performance for oxygen evolution reaction, water decomposition, and metal-air secondary battery oxygen evolution electrocatalytic reaction. Furthermore, it can utilize sunlight to enhance catalytic activity, belonging to a light-assisted high entropy nanocatalyst.
[0060] According to an embodiment of the third aspect of the present invention, there is provided use of the above-mentioned high entropy alloy material as a catalyst or in the preparation of a catalyst.
[0061] According to some embodiments of the present invention, the catalyst is used for oxygen evolution reaction (OER), water decomposition, and metal-air secondary battery oxygen evolution electrocatalytic reaction; preferably, the catalyst is an anode catalyst.
[0062] According to an embodiment of a fourth aspect of the present invention, there is provided an energy storage device comprising the above-mentioned high entropy alloy material.
[0063] According to some embodiments of the present invention, there are at least the following beneficial effects:
[0064] The present invention adopts nanosecond laser technology and utilizes the photothermal conversion characteristics of MXene substrate materials to achieve an instantaneous high temperature environment, quickly prepare a series of (light-assisted) high-entropy alloy nanomaterials, and exhibit excellent catalytic activity (for example, oxygen evolution reaction, oxygen reduction reaction, electrolysis of water oxygen / hydrogen evolution reaction) and cycle stability, greatly improving the efficiency and service life of energy conversion and storage devices. Compared with traditional heating methods, time and economic costs are effectively saved. Compared with carbon material substrates, MXene substrates can provide higher temperatures and avoid phase separation because of their high thermal absorption rate and low thermal emissivity. In addition, by adjusting the relevant parameters of laser irradiation, the structure and size of high-entropy materials can be regulated.
[0065] In addition, the method of the present invention has wide universality. The base material of the present invention can load various types of metals, thereby preparing rich high-entropy nanomaterials, exploring the properties of more unknown materials, and broadening the application field of high-entropy nanomaterials.
[0066] In addition, the preparation method provided by the present invention is simple and easy to operate, has high economic benefits, and is easy to realize industrial large-scale production and application.
[0067] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be obvious from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0069] Figure 1 is a schematic diagram of a laser synthesis device used in Example 1;
[0070] Figure 2 is a graph showing the temperature variation over time of laser rapid preparation assisted by photothermal effect in Example 1;
[0071] Figure 3 is a high-resolution transmission electron micrograph of the light-assisted high-entropy catalyst M-TiO2 / FeCoNiCrMo prepared in Example 1;
[0072] Figure 4 This is a photocurrent response result diagram of the light-assisted high entropy catalyst M-TiO2 / FeCoNiCrMo prepared in Example 1;
[0073] Figure 5 is the ultraviolet absorption spectrum of the light-assisted high entropy catalyst M-TiO2 / FeCoNiCrMo prepared in Example 1;
[0074] Figure 6 It is a comparison chart of the OER performance corresponding to different types of alloys loaded with MXene in Examples 1 to 6 and Comparative Examples 1 and 2.
[0075] Here, HEA represents high-entropy alloys, and V vs. RHE represents the voltage relative to a reference hydrogen electrode. DETAILED DESCRIPTION
[0076] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0077] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention in combination with the specific content of the technical solution.
[0078] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±10%, for example, about 100 is actually 100±10%×100.
[0079] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0080] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0081] The present invention provides a method for preparing a high entropy material by laser heating synthesis, comprising the following steps:
[0082] (1) A metal-based salt solution is used as a precursor solution, loaded on a substrate in a certain proportion, and closely contacts with metal ions through electrostatic adsorption of the functional groups on the surface. After vacuum drying, the solution is placed in a sealed transparent container, and a corresponding atmosphere is introduced according to the product requirements;
[0083] (2) The pulsed laser irradiates the sample surface through the quartz glass above the container. The substrate material converts the laser energy into heat through photothermal conversion. By implementing laser pulses of different powers and scanning speeds, the temperature is instantly raised to 1000-3000K. After the pulsed laser is withdrawn, the temperature rises by about 10 6 The rate of K / s decreases rapidly, and a variety of high-entropy nanomaterials are successfully prepared in different atmospheres.
[0084] The structure of the high entropy material synthesized by the method of the present invention is a homogeneous phase, the composition can be determined by Raman, the crystal phase structure can be determined by XRD and TEM, and the catalytic activity (for example, oxygen evolution reaction, oxygen reduction reaction, oxygen / hydrogen evolution reaction of water electrolysis) and battery charge and discharge performance of the obtained high entropy material can be characterized by an electrochemical workstation and a battery testing system.
[0085] Example 1
[0086] This embodiment provides a method for synthesizing M-TiO2 / FeCoNiCrMo, using Figure 1 The laser synthesis device shown specifically comprises the following steps:
[0087] S1. The substrate (Ti3C2 nanosheets) is etched from Ti3AlC2·MAX according to the following steps:
[0088] 1 g of Ti3AlC2 (purchased from 11 Technology) was added to a mixed solution of 2.5 mL of HF (40 wt%), 6 mL of HCl (36 wt%), and 12 mL of water, stirred at 35° C. for 24 hours, and washed to neutrality after centrifugation; the precipitate was dispersed in 50 mL of water containing 1 g of LiCl, stirred at 35° C. for 4 hours, centrifuged at 5000 rpm, washed three times, and the precipitate was dispersed in 60 mL of deionized water to obtain a Ti3C2 aqueous solution (the measured concentration was 10 mg / mL, and Ti3C2 nanosheets were obtained after further filtration and drying);
[0089] S2. Preparation of mixed metal ion solution:
[0090] Weigh appropriate amounts of FeCl3, CoCl2, NiCl2, CrCl3, and MoCl5 and dissolve them in water to obtain a mixed metal ion solution in which FeCl3, CoCl2, NiCl2, CrCl3, and MoCl5 are all 0.2 mol / L (the ratio of the five metal ions is 1:1:1:1:1);
[0091] Preparation of S3, M-TiO2 / FeCoNiCrMo:
[0092] 4 mL of the mixed metal ion solution obtained in step S2 was added to 10 mL of the Ti3C2 solution obtained in step S1, stirred at room temperature for 30 min at a speed of 300 rpm until the mixture was uniformly mixed, and then freeze-dried; the freeze-dried Ti3C2@FeCoNiCrMo (substrate and metal salt precursor) powder was rolled to a sheet with a thickness of 50 μm, and placed in a device with transparent quartz glass on top and flowing argon gas inside for laser irradiation; wherein the laser wavelength was 1064 nm, the frequency was 30 KHz, the laser pulse width was 10 ns, the scanning speed was 1500 mm / s, and the laser energy density was 2.4 J·cm -2 , laser scanning once, and Ti3C2-derived M-TiO2 / FeCoNiCrMo was obtained.
[0093] During the laser irradiation process, a high-speed temperature meter (IGA6-TV Advanced) was used to detect the pulse laser heating temperature, and the laser power was adjusted based on the pyrolysis temperature of the loaded metal salt precursor. Figure 2 As shown, the laser energy density is 2.4 J·cm -2 The temperature of the Ti3C2 substrate rises to about 2800K within 1ms (heating rate 2.3×10 6 K / s), the ultra-high temperature drives the pyrolysis of metal salts and they are reduced to high entropy alloys by Ti3C2.
[0094] High-resolution transmission electron microscopy was used to examine the internal morphology and structure of the prepared high-entropy nanomaterial M-TiO2 / FeCoNiCrMo. Figure 3 As shown, the interplanar spacings of 0.208 nm and 0.250 nm in the high-resolution transmission electron micrograph correspond to the (111) crystal planes of the high-entropy alloy and the (101) crystal planes of M-TiO2, respectively. The two form a tightly bound heterojunction structure, which is conducive to the rapid transfer of charges.
[0095] The it curves of M-TiO2 / FeCoNiCrMo and TiO2 under illumination and non-illumination conditions were tested using an electrochemical workstation without applying any voltage. Figure 4 As shown, the results show that compared with single TiO2, the M-TiO2 / FeCoNiCrMo ( Figure 4 The M-TiO2 / HEA has a larger photocurrent response, indicating that the strong interaction between the high entropy alloy and TiO2 promotes the rapid transfer of photogenerated carriers.
[0096] The UV-visible absorption spectrum of the prepared light-assisted high entropy catalyst M-TiO2 / FeCoNiCrMo was measured. The results are as follows Figure 5As shown, the UV-visible absorption spectrum shows that compared with single TiO2, Ti3C2-derived TiO2 has a narrower band gap, which increases the light absorption range and is beneficial to improving the photocatalytic performance.
[0097] Example 2
[0098] This embodiment provides a method for synthesizing M-TiO2 / FeCoNiMo, which is carried out with reference to Example 1, except that:
[0099] S2. Preparation of mixed metal ion solution:
[0100] Weigh appropriate amounts of FeCl3, CoCl2, NiCl2, and MoCl5 and dissolve them in water to obtain a mixed metal ion solution with the contents of FeCl3, CoCl2, NiCl2, and MoCl5 each being 0.2 mol / L (the ratio of the four metal ions is 1:1:1:1).
[0101] Example 3
[0102] This embodiment provides a method for synthesizing M-TiO2 / FeCoMo, which is carried out with reference to Example 1, except that:
[0103] S2. Preparation of mixed metal ion solution:
[0104] Weigh appropriate amounts of FeCl3, CoCl2, and MoCl5 and dissolve them in water to obtain a mixed metal ion solution with the contents of FeCl3, CoCl2, and MoCl5 each being 0.2 mol / L (the ratio of the three metal ions is 1:1:1).
[0105] Example 4
[0106] This embodiment provides a method for synthesizing M-TiO2 / FeCo, which is carried out with reference to Example 1, except that:
[0107] S2. Preparation of mixed metal ion solution:
[0108] Weigh appropriate amounts of FeCl3 and CoCl2 and dissolve them in water to obtain a mixed metal ion solution with a concentration of 0.2 mol / L for both FeCl3 and CoCl2 (the ratio of the two metal ions is 1:1).
[0109] Example 5
[0110] This embodiment provides a method for synthesizing M-TiO2 / Fe, which is carried out with reference to Example 1, except that:
[0111] S2. Preparation of mixed metal ion solution:
[0112] Weigh an appropriate amount of FeCl3 and dissolve it in water to obtain a single metal ion solution with a FeCl3 content of 0.2 mol / L.
[0113] Example 6
[0114] This embodiment provides a method for synthesizing MoFeCoNiCrTi, comprising the following steps:
[0115] S1. The substrate (Mo2TiC2) was made of Mo2TiAlC2 (purchased from 11 Technology) and etched with HF at a ratio of (1 g: 20 mL) at 55 °C for 54 hours, and then freeze-dried to obtain Mo2TiC2 powder. Mo2TiC2 was dispersed in deionized water to obtain a Mo2TiC2 aqueous solution (the measured concentration was 10 mg / mL).
[0116] S2. Preparation of mixed metal ion solution:
[0117] Weigh appropriate amounts of FeCl3, CoCl2, NiCl2, and CrCl3 and dissolve them in water to obtain a mixed metal ion solution in which the concentrations of FeCl3, CoCl2, NiCl2, and CrCl3 are all 0.2 mol / L (the ratio of the four metal ions is 1:1:1:1);
[0118] Preparation of S3, MoFeCoNiCrTi:
[0119] 4 mL of the mixed metal ion solution obtained in step S2 was added to 10 mL of the Mo2TiC2 solution obtained in step S1, stirred at room temperature for 30 min at a speed of 300 rpm until the mixture was uniformly mixed, and then freeze-dried; the freeze-dried Mo2TiC2@FeCoNiCr powder was rolled into a sheet with a thickness of 50 μm, and placed in a device with a transparent quartz glass on top and flowing argon gas inside for laser irradiation; wherein the laser wavelength was 1064 nm, the frequency was 30 KHz, the laser pulse width was 10 ns, the scanning speed was 1500 mm / s, and the laser energy density was 2.4 J·cm -2 , laser scanned once to obtain Mo2TiC2-derived Mo2C / FeCoNiCrMoTi.
[0120] The difference between Example 6 and Example 1 lies in the different MXene substrates selected. The Ti3C2 substrate in Example 1 can be derived into TiO2 with photocatalytic activity, and the Mo2TiC2 substrate in Example 5 can be used as a metal source for a high-entropy alloy. The high-entropy alloy formed by in-situ derivatization of the substrate has higher stability, indicating that laser pulse heating technology can be used to select different MXene substrates according to different needs, and different MXene substrates enrich the types of high-entropy alloys.
[0121] Comparative Example 1
[0122] This comparative example provides a method for synthesizing FeCoNiCrMo, which is carried out with reference to Example 1, except that:
[0123] The prepared substrate Ti3C2 nanosheets in step S1 are replaced with carbon nanotubes (CNTs).
[0124] Comparative Example 2
[0125] This comparative example provides a method for synthesizing FeCoNiCrMo, which is carried out with reference to comparative example 1, except that:
[0126] The laser heating in step S3 is replaced by high-temperature tubular furnace heating. The specific scheme for preparing the multi-element alloy by tubular furnace heating is: 100 mg of the substrate loaded with metal ions is placed in a crucible, put into a tubular furnace, and heated to 1300 degrees Celsius at a heating rate of 5°C / min in an argon atmosphere, kept warm for 30 minutes, and then cooled at a rate of 5°C / min.
[0127] The heating rate of the traditional tube furnace is 5℃ / min, while the heating rate of the laser heating technology is 10 6 ℃ / min, the ultrafast heating method is conducive to the formation of high entropy structure, while the rapid cooling method avoids excessive particle growth and phase separation.
[0128] Test Case
[0129] The multi-component alloy materials prepared in all the embodiments and comparative examples were tested according to the following test scheme.
[0130] 1. Photo-assisted OER catalytic performance test
[0131] Using a rotating disk and an electrochemical workstation, a three-electrode system was used, with 1 M KOH as the electrolyte, Hg / HgO as the reference electrode, and a carbon rod as the counter electrode. The material was prepared into a solution (2 mg of the material was dispersed in a mixed solvent formed by 160 μL of water, 160 μL of ethanol, and 40 μL of Nafion) and dropped onto the carbon as the working electrode. The working electrode area was 1 cm -2 , the loading amount is 0.25 mg cm -2 , respectively test the oxygen evolution reaction (OER) overpotential. The test method is to use Chenhua electrochemical workstation to test the cyclic voltammetry curve, the test range is 0-0.8V, and the scan rate is 10mV·s -1 The catalyst stability was tested using a constant current test method, with the current set to 10 mA cm -2 , record the voltage change over time. Use a xenon lamp to provide 100mW·cm -2 of light to simulate sunlight and test the OER performance under light.
[0132] The test results are shown in Table 1.
[0133] Table 1
[0134]
[0135] The smaller the Tafel slope, the faster the charge transfer, the faster the reaction kinetics, and the better the catalytic performance. As shown in Table 1, in Examples 1 to 4, the Tafel slope is effectively reduced under illumination conditions, indicating that TiO2 derived from Ti3C2 after laser irradiation can effectively absorb sunlight, generate photogenerated carriers, and improve the OER reaction kinetics.
[0136] In addition, from Table 1 and Figure 6 It can be seen that by using laser combined with the excellent photothermal conversion effect of Ti3C2 substrate, the present invention successfully synthesized a variety of multi-element alloy catalysts. With the increase of metal types, the material entropy increases and the overpotential gradually decreases, indicating that the synergistic effect of various ions promotes charge transfer, and the synergistic effect of various metal ions promotes the improvement of catalytic activity, specifically, effectively improving the performance of catalytic OER. At the same time, the Ti3C2 substrate is derived from TiO2 in situ, which plays a photocatalytic role and further improves the OER catalytic activity. On the other hand, there is a strong interaction between the in-situ derived TiO2 and the high entropy alloy, which promotes the improvement of catalyst stability. The difference between Example 5 and Example 1 is that different MXene substrates are selected. The results show that the transition metals in the MXene substrate affect the formation of the loaded alloy, and Mo2TiC2 forms MoFeCoNiCrTi high entropy alloys with the loaded metal ions, and has excellent catalytic activity and stability. Compared with the comparative example, the high entropy alloy material synthesized by the present invention using the MXene substrate can effectively use sunlight to assist in improving the OER catalytic activity. From the comparison between Example 1 and Comparative Example 1, it can be seen that compared with the carbon material substrate, the MXene substrate can provide a higher temperature because the MXene substrate has a high thermal absorptivity and a low thermal emissivity, and the carbon material generally has the characteristics of high absorption and high emission. On the other hand, the carbon material substrate cannot achieve photocatalysis. Therefore, the carbon material substrate limits the temperature and heating rate of laser heating, which is not conducive to the preparation of high entropy nanomaterials.
[0137] 2. Performance testing in zinc-air batteries
[0138] The material, Super P, and polytetrafluoroethylene (PTFE) were mixed and ground in a ratio of 80:20:1.5, rolled into thin sheets, loaded on the current collector, and assembled into a zinc-air battery with zinc sheets and an electrolyte containing 6M KOH and 0.2M Zn(CH3COO)2. The battery was tested using a NEWER electrochemical workstation at 10mA·cm -2Charge-discharge cycle performance at current density, xenon lamp provides 100mW·cm -2 of lighting to simulate sunlight.
[0139] The test results are shown in Table 2.
[0140] Table 2
[0141]
[0142]
[0143] As can be seen from Table 2, consistent with the OER test, the light-assisted high entropy catalyst synthesized in the present invention exhibits excellent catalytic activity in catalyzing the oxygen evolution reaction of metal-air batteries, effectively reducing the reaction energy barrier, and improving the energy conversion and storage efficiency. At the same time, the high entropy makes it have excellent cycle stability. Therefore, the materials with good performance selected by the light-assisted OER catalytic performance test also have good zinc-air battery performance.
[0144] The above content describes the embodiments of the present invention in detail in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing a high entropy alloy material, characterized in that: The following steps are involved: A precursor solution containing a metal salt is mixed with a dispersion of MXene, and the mixture is dried to obtain a MXene loaded with a metal precursor; and the MXene loaded with a metal precursor is subjected to laser irradiation to prepare the high entropy alloy material.
2. The preparation method according to claim 1, characterized in that: The process conditions of the laser irradiation include at least one of the following (a)-(f): (a) The wavelength of the laser is 248 to 1064 nm; (b) The power of the laser is 1 to 100 W; (c) The laser spot diameter is 10 to 1000 μm; (d) The pulse frequency of the laser is 10 to 100 KHz; (e) The pulse width of the laser is 5 to 100 ns; (f) The scanning speed of the laser is 100 to 3000 mm / s.
3. The preparation method according to claim 1, characterized in that: The MXene is selected from at least one of Ti3C2 and Mo2TiC2.
4. The preparation method according to claim 1, characterized in that: The metal salt is selected from at least one of cobalt salts, iron salts, nickel salts, chromium salts and molybdenum salts.
5. The preparation method according to claim 1, characterized in that: The ratio of the molar amount of the metal salt to the mass of the MXene is 1-100 mM:1 g.
6. The preparation method according to claim 5, characterized in that: The concentration of the metal salt in the precursor solution is 0.1 to 2 mol / L; and / or the concentration of MXene in the dispersion is 2 to 50 mg / mL.
7. The preparation method according to claim 1, characterized in that: The laser irradiation is performed under a protective gas atmosphere, and the protective gas is selected from one of argon, a mixed gas of argon and oxygen, a mixed gas of argon and hydrogen, and ammonia.
8. The preparation method according to claim 1, characterized in that: The MAX original phase is etched with hydrofluoric acid to obtain the MXene.
9. A high entropy alloy material, characterized in that: The high entropy alloy material is prepared by the preparation method described in any one of claims 1 to 8.
10. Use of the high entropy alloy material according to claim 9 as a catalyst or in the preparation of a catalyst.